الثورة والتغيير السياسي في مسرح سعد الله ونوس - عزوزي أسماء (My University, 2025)
Abstract: Theatre is one of the arts that has a close connection to society, and thus it is the mirror that reflects reality and its various issues. It has been present throughout the ages in the lives of peoples and has played many roles, encompassing various aspects of life. Thus, various types of theatre have emerged, including political theatre or the theatre of politicization, which is associated with the late creative artist Saadallah Wannous. It emerged as a result of the deterioration of political and social conditions. From here, our study entitled "Revolution and Political Change in Saadallah Wannous's Theatre Through Selected Models" was founded. The importance of this study lies in understanding the relationship between theater and politics, on the one hand, and between theater and society, on the other. It also emphasizes the role theater plays in becoming an effective tool for critiquing political and social conditions and motivating and pushing the masses toward change. The work plan for this study consists of an introduction and two chapters. The introduction serves as a gateway to the study and provides a brief overview of Saadallah Wannous's life and the stages of his theater's development. The first chapter, entitled "Theater and Politics," defines theater from a linguistic and technical perspective, defines revolution linguistically and technically, and outlines its causes, dimensions, and goals. It also addresses the definition of change, its causes, methods, and goals. It then moves on to a study of political theater (its definition, emergence, and pioneers), and outlines its most important goals. Finally, it discusses the theater of politicization in Saadallah Wannous. This is the theoretical aspect. As for the second chapter, titled "The Political Dimensions in the Plays "The Adventure of the Mamluk Jaber's Head" and "The Elephant, O King of the Ages," it was an applied study in which a summary of each play was presented, along with an examination of the characters, time, place, events, language, and symbols. It then moved on to examine the issues addressed by Saadallah Wannous in the two plays and the political dimensions embodied in them, along with an examination of heritage and the manifestations of the influence of Brecht on Wannous's theater. Finally, it examined the manifestations of revolution and political change in the two plays. Through this study, we reached a set of conclusions, the most important of which is that theater is both a text and a performance. However, if this text is not presented to an audience and is not presented using different techniques, it remains a mere discourse with no impact. The two plays also convey an image of the oppression and political injustice practiced by corrupt authorities against the Arab peoples, and they convey the stance of these peoples, represented by silence and a refusal to confront them. -------------------- الملخص: يعد المسرح من الفنون التي لها صلة وثيقة بالمجتمع، وبذلك فهو المرآة التي تعكس الواقع وقضاياه المختلفة فقد كان حاضرا على مر العصور في حياة الشعوب وأدّى أدوارا عديدة، شملت مختلف مناحي الحياة وظهرت بذلك أنواع للمسرح من بينها المسرح السياسي أو مسرح التّسييس الذي ارتبط بالمبدع الراحل "سعد الله ونوس" وظهر نتيجة لتدهور الأوضاع السياسية والاجتماعية، ومن هنا تأسست دراستنا المعنونة ب " الثورة والتغيير السياسي في مسرح سعد الله ونوس من خلال نماذج مختارة". وتكمن أهمية هذه الدراسة في فهم العلاقة بين المسرح والسياسة من جهة وبين المسرح والمجتمع من جهة أخرى وكذلك التأكيد على الدور الذي يلعبه المسرح في كونه أصبح أداة فاعلة في نقد الأوضاع السياسية والاجتماعية وتحفيز الجماهير ودفعها نحو التغيير، أما بالنسبة لخطة العمل الخاصة بهذه الدراسة فقد تجسدت في مدخل وفصلين وكان المدخل بمثابة بوابة للدراسة وقد تناول نبذة عن حياة سعد الله ونوس ومراحل تطور مسرحه، أما بالنسبة للفصل الأول والمعنون ب " المسرح والسياسة " فقد تم فيه تحديد المسرح من الناحية اللغوية والاصطلاحية وتعريف الثورة لغة واصطلاحا وذكر أسبابها وأبعادها وأهدافها، وكذلك تناول تعريف التغيير مع ذكر أسبابه وطرائقه وأهدافه، ثم الانتقال إلى دراسة المسرح السياسي(تعريفه، ظهوره، رواده) وذكر أهم أهدافه، وصولا إلى مسرح التّسييس عند "سعد الله ونوس"، هذا فيما يخص الجانب النظري. أما بالنسبة للفصل الثاني والمعنون ب "الأبعاد السياسية في مسرحيتي "مغامرة رأس المملوك جابر" و "الفيل يا ملك الزّمان" فقد كان دراسة تطبيقية تم فيها تقديم ملخص لكل من المسرحيتين ودراسة الشخصيات والزمان والمكان والاحداث واللغة والرمز، والانتقال إلى القضايا التي عالجها سعد الله ونوس في المسرحيتين والأبعاد السياسية التي تجسدت فيهما مع دراسة التراث ومظاهر تأثر مسرح ونوس بمسرح "بريخت"، وصولا إلى دراسة تجليات الثورة والتغيير السياسي في المسرحيتين. وقد توصلنا من خلال هذه الدراسة إلى مجموعة من النتائج أهمها أن المسرح نص وعرض في آن واحد، لكن هذا النص إذا لم يعرض أمام الجمهور ولم يقدّم بتقنيات مختلفة، يظلّ مجرد خطاب ليس له تأثير، وكذلك تنقل لنا المسرحيتين صورة القهر والظلم السياسي الذي تمارسه السلطة الفاسدة ضد الشعوب العربية، كما تنقل لنا موقف هذه الشعوب المتمثّل في الصمت ورفض المواجهة. ----------------------------- Résumé: Le théâtre est l'un des arts les plus étroitement liés à la société. Il est ainsi le miroir de la réalité et de ses enjeux. Présent de tout temps dans la vie des peuples, il a joué de nombreux rôles, englobant divers aspects de la vie. Ainsi, différents types de théâtre ont émergé, notamment le théâtre politique ou théâtre de politisation, associé au regretté artiste Saadallah Wannous. Il est né de la dégradation des conditions politiques et sociales. C'est de là qu'est née notre étude intitulée « Révolution et changement politique dans le théâtre de Saadallah Wannous à travers une sélection de modèles ». L'importance de cette étude réside dans la compréhension des relations entre théâtre et politique, d'une part, et entre théâtre et société, d'autre part. Elle souligne également le rôle du théâtre comme outil efficace de critique des conditions politiques et sociales, et de motivation et d'impulsion des masses vers le changement. Le plan de travail de cette étude comprend une introduction et deux chapitres. L'introduction sert de porte d'entrée à l'étude et offre un bref aperçu de la vie de Saadallah Wannous et des étapes de développement de son théâtre. Le premier chapitre, intitulé « Théâtre et politique », définit le théâtre d'un point de vue linguistique et technique, définit la révolution sur les plans linguistique et technique, et en expose les causes, les dimensions et les objectifs. Il aborde également la définition du changement, ses causes, ses méthodes et ses objectifs. Il aborde ensuite une étude du théâtre politique (sa définition, son émergence et ses pionniers) et en expose les principaux objectifs. Enfin, il aborde le théâtre de la politisation chez Saadallah Wannous. Il s'agit de l'aspect théorique. Quant au deuxième chapitre, intitulé « Les dimensions politiques des pièces « L'Aventure de la Tête du Mamelouk Jaber » et « L'Éléphant, ô Roi des Âges », il s'agissait d'une étude appliquée présentant un résumé de chaque pièce, ainsi qu'une analyse des personnages, de l'époque, du lieu, des événements, de la langue et des symboles. Il abordait ensuite les questions abordées par Saadallah Wannous dans les deux pièces et les dimensions politiques qu'elles incarnent, ainsi qu'une analyse de l'héritage et des manifestations de l'influence de Brecht sur le théâtre de Wannous. Enfin, il examinait les manifestations de la révolution et du changement politique dans les deux pièces. Cette étude nous a permis de tirer plusieurs conclusions, dont la plus importante est que le théâtre est à la fois un texte et une performance. Cependant, si ce texte n'est pas présenté au public et n'est pas présenté selon des techniques différentes, il reste un simple discours sans impact. Les deux pièces véhiculent également une image de l'oppression et de l'injustice politique exercées par des autorités corrompues contre les peuples arabes, et traduisent la position de ces peuples, incarnée par le silence. et un refus de les affronter
Keywords: Saadallah Wannous; political theatre; politicization; revolution and political change.; سعد الله ونوس، المسرح السياسي، التسييس، الثورة والتغيير السياسي; théâtre politique; politisation; révolution et changement politique.